Silencing and overexpression of human blood group antigens in transfusion: Paving the way for the next steps. Issue 3 (May 2015) - Bagnis, Claude
Abstract: In the field of transfusion, controlling expression of blood group system antigens on the surface of RBCs has been envisioned as a major research objective for five decades. With the advent of gene transfer techniques in the 1980s, genetic manipulation acquired the tools and know-how necessary to propose this goal along with other strategies. Besides the use of gene transfer to study blood group antigens and to develop tools for transfusion purposes, since the beginning of the new millennium, technological advances in combination with the recognition of the clinical potential of gene transfer have led the transfusion domain into development of cell therapy approaches for therapeutic purposes based on genetic manipulation.